Managemnet of Fournier’s Gangrene at Department of Urology Chandka Medical College Hospital - Hameed-ur-Rehman Bozdar, Aamir Ali Shaikh, Riaz Hussain, Naveed Ahmed Shaikh, Khob Chand Rohra, Nisar Ahmed Shaikh, Amanullah Abassi (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and object: To assess the aetiology and management of Fournier’s gangrene. Methodology: We examined 30 paients retrospectivdely, during the period from 2015 to 2020, the patients from the Urology department of CMC Hospital at SMBB Medical University Larkana. All the related data were taken as well as demographic details, history and risk factor from the patients regarding illness. Routine investigation carried out including Blood CP ESR, Urine Dr, Blood sugar, Renal profile and pus culture sensitivity. 20 patients under gone for surgical debridement, 5 patients require skin grafting and 4 patients requires testes burrial after recovery under aseptic measures. Result: 30 male patients with mean age 20±10.5 year. Majority (80%) of patient presenting with necrotising infection on scrotum,perineum and hypogatric area. Basic laboratory investigations including Blood CBC showed mean WBC 15000/cmm3, mean Hb was 8.5 gms, Urine analysis showed pyuria and haematuria, pus culture and sensitivity positive in 90% cases and most prevalent organism was E.Coli, Mean Blood urea was 35mg and serum creatinine was 1.9mg. Commonest causes of fourneir gangreen was trauma, UTI, urethral stricture, indewelling catheter and perianal abcess and D.M was commonest comorbidity). All patients treated by surgical debridement while 5 patients requires skin grafting and 4 patients requires testes burrial after recovery under aseptic measures with with triple regimen antibiotics. Conclusion: Surgical debridment of necrotic tissues and triple regimen antibiotic are the main stay for primary management of Fournier’s gangrene (FG) to decrease the morbidity and mortality keywords: Fournier’s Gangrene, surgical debriment, and triple regimen antibiotics.